2011
DOI: 10.1177/0269216311418709
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the role of fish oil for the treatment of cachexia in advanced cancer: An EPCRC cachexia guidelines project

Abstract: Background: The European Palliative Care Research Collaboration is developing clinical guidelines on cachexia in patients with advanced cancer. A systematic review on the use of fish oil/omega-3-fatty acids (n-3-FA)/eicosapentaenoic acids (EPA) in advanced cancer patients suffering from cancer cachexia was performed as part of the guideline development. Methods: The systematic literature search in Medline on the use of fish oil/n-3-FA/EPA identified 244 papers, with 38 publications included in the final evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 47 publications
(133 reference statements)
0
58
0
7
Order By: Relevance
“…This multimodal approach would incorporate oral nutritional supplements, exercise and anti-inflammatory medications and has been advocated in the prevention and treatment of CC. Underpinning this approach are meta-analyses suggesting that each of the interventions components, while not unequivocally associated with improved outcome, is more likely than not to be beneficial (77,88,91,94,95) . The MENAC trial (a multimodal intervention of exercise, nutrition and anti-inflammatory medication plus standard care v. standard care alone) to prevent/attenuate cachexia will test the efficacy of a multi-dimensional approach during chemotherapy.…”
Section: Multimodal Approachesmentioning
confidence: 99%
“…This multimodal approach would incorporate oral nutritional supplements, exercise and anti-inflammatory medications and has been advocated in the prevention and treatment of CC. Underpinning this approach are meta-analyses suggesting that each of the interventions components, while not unequivocally associated with improved outcome, is more likely than not to be beneficial (77,88,91,94,95) . The MENAC trial (a multimodal intervention of exercise, nutrition and anti-inflammatory medication plus standard care v. standard care alone) to prevent/attenuate cachexia will test the efficacy of a multi-dimensional approach during chemotherapy.…”
Section: Multimodal Approachesmentioning
confidence: 99%
“…A systematic review of clinical trials on the therapeutic role of omega-3 FA consumption (EPA and DHA) on cancer cachexia showed that at least 1.5 g per day for more than 8-weeks period improve appetite, body lean mass, functional status, quality of life and decrease inflammatory mediators [234]. However, the available clinical data about effect of single-agent EPA on cancer cachexia are controversial and, due to lack of sufficient evidence, it is not easy to make a clear decision about its application as single agent [235][236][237][238]. However, the promising role of omega-3 FAs on acute phase responses after surgery and inhibition of protein degradation is publicized [239,233].…”
Section: Cancer Cachexiamentioning
confidence: 99%
“…However, measuring quality of life remains controversial (10). It is not appropriate to focus on feeding without anticipating changes in physiological and psychosocial behavior (11). On the contrary, optimal nutrition in combination with systemic antiinflammatory treatment and erythropoietin improves the survival of underweight malignant patients (12,13).…”
Section: Introductionmentioning
confidence: 99%